Selection of the best solvent and pH indicator for the acid-base titration of indomethacin in laboratories for pharmacy college students - Luma A. Musa; Hussien A. Karim; Ahmed M. Ahmed (Genius Journals, 2022)
To test a number of solvents and pH indicators in the acid-base titration of indomethacin drug and select the best ones of them that will give the best results than the usual solvent and indicator used in the designed acid-base titration of indomethacin.
Keywords: Acid-Base Titration; Indomethacin; Ph Indicators; Activity